Contrasting motivation and learning strategies of ex-mathematics and ex-mathematical literacy students - Baumgartner, W.L.; Spangenberg, E.D.; Jacobs, G.J. (South African Journal of Higher Education, 2018)
This inquiry contrasts motivation and learning strategies of ex-Mathematics (Maths) and ex-Mathematical Literacy (ML) students. ML ideally delivers candidates who can make sense of and actively participate in a world of numbers and numerical arguments, but ex-ML students are excluded from many undergraduate studies at most South African higher education institutions (HEIs). Institutions employ various strategies in enhancing student transition to higher education (HE), however, such options are rare for ex-ML students. A year-long foundation programme offered by a private HEI is one exception. This inquiry employed the Motivated Strategies for Learning Questionnaire and t-test, detecting significant differences in motivation and learning strategies between 111 ex-Maths and 81 ex-ML students. The intrinsic goal orientation, task value, self-efficacy, effort regulation and test anxiety-handling abilities of ex-Maths students were significantly superior. The article offers insights into strategies that might improve the motivation of ex-ML students in support of their academic development.